DNA methylation patterns in mammals - Greally, John (Henry Stewart Talks, 2011)
The distribution of cytosine methylation in mammals, Influences on targeting of cytosine methylation, Demethylation of DNA, Protection against cytosine methylation, Global and developmental dynamics of cytosine methylation, Patterns of change of cytosine methylation in disease, Influence of DNA sequence polymorphism on cytosine methylation variability, Future directions